Islamic Social Reporting (ISR) Analysis in Indonesia and Malaysia - Wiwit Ayu Nofitasari; Hikmah Endraswati (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
The purposes of this study are to examine the effect of company size, profitability, board of commissioners, proportion of independent commissioners, and frequency of meetings on the level of Islamic Social Reporting (ISR) in Indonesia and Malaysia and to test whether there is difference ISR in Indonesia and Malaysia. The sample of this study are 10 companies that issued sukuk at Indonesia Shariah Stocks Index and 8 companies on Malaysia Stock Exchange in 2013-2017. Multiple regression and different tests are used in this research as analysis techniques. The results show that the size of the company effects on the level of ISR in Indonesia positively but not in Malaysia. Profitability, board size, and the proportion of independent commissioners does not effect on ISR levels in Indonesia and Malaysia. The frequency of board of commissioners meetings effect on ISR levels in Indonesia and Malaysia positively and there is difference ISR in Indonesia and Malaysia. The implication of this research is that there is a need for regulations that regulate ISR disclosure in Indonesia to improve the quality of ISR disclosure to the stakeholders